Pancasila Legal System: Balancing The Fulfillment Of National Moral Values And Law Enforcement In Indonesia: Sistem Hukum Pancasila: Menyeimbangkan Pemenuhan Nilai Moral Nasional dan Penegakan Hukum di Indonesia. - Esfandiari, Fitria; Widianto, Aan Eko (Indonesian Journal of Law and Economics Review, 2024)
This normative research delves into the Pancasila legal system in Indonesia, evaluating its impact on the nation's moral values and the enforcement of law. Pancasila, embodying the core principles of Indonesian society, encompasses values such as divinity, humanity, unity, democracy, and justice. Despite its significance, the study argues that the Pancasila legal system has yet to manifest substantially in the fabric of national life. The research, employing literature review methodology, positions Pancasila as a philosophy guiding law enforcement, urging a reevaluation of legal systems rooted in the wisdom of societal values. The imperative lies in bridging the gap between legal certainty and substantive justice, fostering a legal framework that resonates with the cultural richness of Indonesian society. This research advocates for a critical examination of the legal system, rooted in indigenous wisdom, to better align it with the aspirations of the nation and its people. Highlights: Cultural Foundations: The research critically examines the Pancasila legal system, emphasizing its role as a crystallization of Indonesia's cultural values, including divinity, humanity, unity, democracy, and justice. Guiding Philosophy: Pancasila is positioned as a guiding philosophy for law enforcement, highlighting its potential to shape the ethical foundation and moral compass of legal practitioners in Indonesia. Call for Reevaluation: The study advocates for a reevaluation of the legal system, urging a return to indigenous wisdom and cultural values to bridge the gap between legal certainty and substantive justice in Indonesian society. Keywords: Pancasila, Legal System, Moral Values, Law Enforcement, Indonesia